(untitled) (Sustainability in Debate, 2011)
The analysis of sustainability is a big scientific challenge, especially in Amazônia, a region which has become a kind of open-air laboratory where many conceptions of what is sustainability are currently being tested. The unveiling of recurring effects in these experiments, which could constitute key factors of sustainability in the context of tropical forests, was the main objective of the DURAMAZ research project, which analyzed the local geographical, social, demographical or economic impacts of 13 projects of sustainable development throughout the Amazon. We present in this text the key points of the methodology, especially the construction of an ad-hoc indicator system, grounded on the databases elaborated from the information collected in the field, and some conclusions we were able to reach about sustainability in the Brazilian Amazon region.